The contribution of a 'whole of government' smoke-free policy on the island of St Helena - Angela Mary Jackson-Morris (Taylor & Francis Group, 2019)
Under its Health Promotion Strategic Framework 2018-19 the St Helena Government prioritised action to address smoking and obesity to reduce a high non-communicable disease burden. The first tobacco control measure was a policy, 'Smoke-Free Government' (SFG), to create smoke-free public outdoor and indoor sites across all sites and services for staff and public users, abolish 'official' staff 'smoking breaks', and establish and promote community-wide cessation support. This paper assesses the perceived acceptability and preliminary impact of SFG in St Helena 2018-19. An online survey of government staff was undertaken 6 months post-SFG implementation to obtain insight into perceived impact, implementation, and acceptability. A population-wide health survey provided smoking prevalence and quit data prior to, and 11 months post-implementation. A majority of staff believed the policy contributed to reducing smoking, was generally observed, accepted, and entailed one or more positive effects, including reduced second-hand smoke exposure, increased quit attempts, and reduced disruption from 'smoke-breaks'. Recommendations were consistent enforcement and expanded quit support. Population data for the SFG period indicated that smoking, and particularly daily smoking declined, quit intentions increased, and quit attempts almost doubled. The SFG policy appears to have contributed positively towards stronger tobacco control in St Helena in 2018-19.